Accounting Noise and the Pricing of Cocos - Mike Derksen; Peter Spreij; Sweder van Wijnbergen (Tinbergen Institute, 2018)
Contingent Convertible bonds (CoCos) are debt instruments that convert into equity or are written down in times of distress. Existing pricing models assume conversion triggers based on market prices and on the assumption that markets can always observe all relevant firm information. But all Cocos issued sofar have triggers based on accounting ratios and/or regulatory intervention. We incorporate that markets receive information through noisy accounting reports issued at discrete intervals, which allows us to distinguish between market and accounting values, and between automatic triggers and regulator-mandated conversions. Our second contribution is to incorporate that coupon payments are contingent too: their payment is conditional on the maxumum Distributable Amount not being exceeded. We examine the impact of CoCo design parameters, asset volatility and accounting noise on the price of a CoCo; and investigate the interaction between CoCo design features, the capital structure of the issuing bank and their implications for risk taking and investment incentives. Finally, we use our model to explain the crash in coco prices after Deutsche Bank's profit warning february 2016.
Keywords: G12; G13; G18; G21; G28; G32; 330; Contingent capital pricing; accounting noise; Coco triggers; Coco design; risk taking incentives; investment incentives